Etourism advertising effectiveness: banner type and engagement as moderators. Issue 4 (9th July 2018) - Muñoz-Leiva, Francisco; Liébana-Cabanillas, Francisco; Hernández-Méndez, Janet
Abstract : Purpose: This paper aims to analyze advertising effectiveness in terms of self-reported memory (recall) by measuring customers' visual attention, including consumer engagement with e-tourism 2.0 tools and the banner type used as moderating variables. Design/methodology/approach: Data were collected through a within-subject, between-groups experimental design based on eye-tracking methodology, followed by a self-administered questionnaire. Participants were instructed to visit three e-tourism tools, namely, a hotel's blog, a social network (i.e. Facebook) page and a virtual community (i.e. TripAdvisor) page. Findings: This research uncovers the main determinants of consumers' self-reported recall of banner ads. The study offers empirical insight regarding the positive impact of fixation counts and visit duration on consumer recall. The findings also reveal that the impact of these measurements on consumer recall is moderated by the level of animation of the advertisement, while the number of fixations is moderated by the level of consumer engagement. Overall, the results suggest the usefulness of eye-tracking methodology in assessing the advertising effectiveness of e-tourism tools. Research limitations/implications: The practical implications identified in this research, along with its limitations and future research opportunities, are of interest both for further theoretical development and practical applications. Scholars are therefore encouraged to further test the research propositions, including in longitudinal or mobile/smartphone-based research. Originality/value: The authors offer a pioneering attempt in the application of eye-tracking methodology to online, e-tourism-based service innovations and examine the possible impact of visual marketing stimuli and their effects on user social network-related behavior.